Menggagas Revitalisasi Nilai Nilai Pancasila dalam Peran Masyarakat terhadap Generasi Muda Berbangsa dan Bernegara - Tity Kusrina; Mursyidah Dwi Hartati (Cakrawala: Jurnal Pendidikan, 2019)
The problem of youth is an eternal problem and is always experienced by each generation in relation to older generations. The problem was caused due to the result of the process of maturity, adjusting himself to the new situation arises the hope that every young man will have a better future than his parents. The research objectives (1) describe the idea of revitalizing Pancasila values of the role of the community, (2) describe the understanding of the role of society towards the young generation of the nation and state, (3) describe the idea of revitalizing the Pancasila values of the role of the community towards the nation's young generation and the state. This type of research is a qualitative study using a descriftive approach. The subject of this research is the Young Generation of Tegal City, Tegal Barat Subdistrict in 2019. The data analysis of this study uses Triangulation. The results of this study indicate that the revitalization of the values of Pancasila in the context of the current era, as the young generation has great control in social life in the present and future in order to realize and practice the values of Pancasila. So it is appropriate for the young generation of both men and women to be a wise generation in various aspects of life in accordance with the values of Pancasila both practice in the family, community, and country.